Leea macrophylla Roxb. leaf extract potentially helps normalize islet of β‐cells damaged in STZ‐induced albino rats. Issue 4 (30th March 2018) - Rahman, Md. Atiar; Chowdhury, J. M. Kamirul Hasan; Aklima, Jannatul; Azadi, Mohammad Ali
Abstract: This research aims to investigate the protective effects Leea macrophylla Roxb polyphenols on streptozotocin‐induced diabetic rats. Polyphenolic assays were undertaken through established methods. To conduct animal intervention study, forty Wistar albino male rats (average body weight 188.42 ± 7.13 g) of different groups were diabetized by streptozotocin (60 mg/kg) only in the animals of diabetic control (DC) and L. macrophylla extract (LM) groups. At the end of 4 weeks of intervention, serum was analyzed for insulin, liver and cardiac enzymes, lipid profiles, uric acid, and creatinine using ELISA method. In vitro α‐amylase inhibition of LM was evaluated and compared with reference drug acarbose. Pancreatic tissues were undertaken for histopathological screening. Food and fluid intake, weekly blood glucose level, liver glycogen, aspartate transaminase (AST), creatinine kinase (CK‐MB), cholesterol, and lactate dehydrogenase (LDH) were significantly decreased, whereas oral glucose tolerance (OGTT) ability, serum insulin concentration, and pancreatic islets morphology were significantly improved in the LM300 treatment group compared to the DC group. Alpha‐amylase inhibition was not found to be very promising for guiding the α‐amylase inhibition pathway. Results suggest that L. macrophylla can exert a potential effort to restore pancreatic β‐cell damaged by streptozotocin induction. Abstract : This article has investigated the effect of polyphenolic content of Leea macrophylla leaf extract, a very useful medicinal plant, on the pancreatic cells in streptozotocin‐induced diabetes mellitus. This research also comprehensively studies the effect on other diabetes and diabetes‐related parameters to establish the plant as alternative source of foods and nutrition to control diabetes.